Research progress and challenges of two dimensional MoS2 field effect transistors. (October 2018) - Divya Bharathi, N; Sivasankaran, K
Abstract: This review paper gives an outline of the recent research progress and challenges of 2D TMDs material MoS2 based device, that leads to an interesting path towards approaching the electronic applications due to its sizeable band gap. This review presents the improvement of MoS2 material as an alternate to a silicon channel in a transistor with its excellent energy band gap, thermal conductivity, and exclusive physical properties that are expected to draw attention to focusing on semiconducting devices for most futuristic applications. We discuss the band structure of MoS2 for a different number of layers with its structure, and various synthesis techniques of the MoS2 layer are also reviewed. The MoS2 based field effect transistor has attracted a great deal of attention due to its excellent properties such as mobility, on/off current ratio, and maximum on-current of the devices. The transition of mobility as a function of temperature and thickness dependence are also discussed. However, the mobility of MoS2 material is large in bulk form and lower in monolayer form. The use of a high- k gate dielectric in MoS2 FET is used to enhance the mobility of the device. Different metal contact engineering and different doping techniques were deployed to achieve low contact resistance. This review paper focuses on various aspects of layered TMDs material MoS2 based field effect transistors.